פתרו (x + 1) (x + 3) (x + 4) (x + 6) = 112?

פתרו (x + 1) (x + 3) (x + 4) (x + 6) = 112?
Anonim

תשובה:

# x = -7 / 2 + -isqrt31 / 2 # או # x = -7 / 2 + -sqrt57 / 2 #

הסבר:

תן לנו קבוצה LHS כמו

# (x + 1) (x + 6) (x + 3) (x + 4) = 112 #

# => (x ^ 2 + 7x + 6) (x ^ 2 + 7x + 12) = 112 #

עכשיו בואו # u = x ^ 2 + 7x # ולאחר מכן משוואה לעיל הופך

# (u + 6) (u + 12) = 112 #

או # u ^ 2 + 18u + 72 = 112 #

או # u ^ 2 + 18u-40 = 0 #

או # (u + 20) (u-2) = 0 # כלומר # u = 2 # או #-20#

ככזה גם # x ^ 2 + 7x + 20 = 0 # כלומר #x = (- 7 + -sqrt (7 ^ 2-80)) / 2 # כלומר # x = -7 / 2 + -isqrt31 / 2 #

או # x ^ 2 + 7x-2 = 0 # כלומר #x = (- 7 + -sqrt (7 ^ 2 + 8)) / 2 # כלומר # x = -7 / 2 + -sqrt57 / 2 #